PENGARUH EDUKASI PERAWATAN JANGKA PANJANG PADA LANSIA DENGAN PENGETAHUAN KADER KESEHATAN DI AREA KOMUNITAS - Thomas Erjinyuare Aquino Amigo; Cornelia Dede Yoshima Nekada (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2019)
The elderly population which increases rapidly along with the downgrading of various systems generate impacts on the health condition of the elderly, thus, long-term care is required. The long-term care requires health cadres or caregivers who support the health workers, however, health cadres or caregivers need to conceive a decent knowledge regarding long-term care on the elderly. According to this phenomenon, therefore, the researchers were interested to conduct a study concerning the impact of the long-term care education for elderly on the knowledge of health cadres. This research aimed to discover the impact of long-term care education for elderly on the knowledge of health cadres in Pokoh Hamlet, Wedomartani, Ngemplak, Sleman, Yogyakarta Special Region. The research was performed through a quasi-experimental method with nonequivalent control group pre and posttest design. The knowledge of the respondent was measured before the education regarding long-term care is provided, then, the respondents were educated, and the knowledge of cadre about long-term care was measured at end of the meeting. Respondents involved in this research were individuals who follow the education and cadres or local people who nurse the elderly. The knowledge of cadres was measured through the questionnaire of long-term care. The statistical hypothesis test was performed on the obtained data through Wilcoxon’s test. A total sampling was used as the sampling technique in this research which resulted in 16 respondents as the sample. The results of this research indicated that the median score of the knowledge of health cadres was 39.5 before the intervention and 45 after the intervention with 0.000 of p-value, there was a significant difference of knowledge between before and after the long-term care education was given on health cadres. The conclusion is that there was a significant difference between the long-term care education with the knowledge of health cadres. Health cadres are expected to be able of performing screening on elderly who require long-term care and also capable of performing long-term care on the elderly which focused on the fulfillment of basic needs.